2000
DOI: 10.1162/089892900562156
|View full text |Cite
|
Sign up to set email alerts
|

A Fronto-Posterior Network Involved in Visual Dimension Changes

Abstract: Objects characterized by a unique visual feature may pop out of their environment. When participants have to search for such “odd-one-out” targets, detection is facilitated when targets are consistently defined within the same feature dimension (e.g., color) compared with when the target dimension is uncertain (e.g., color or motion). Further, with dimensional uncertainty, there is a cost when a given target is defined in a different dimension to the preceding target, relative to when the critical dimension re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
103
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 45 publications
14
103
1
3
Order By: Relevance
“…Dimension changes further elicited activation along the descending and horizontal segments of the intraparietal sulcus, whereas response changes led to activation in its ascending segment. This distribution is in good agreement with studies of visual attention shifts, both between locations and between features, which have consistently reported activation along the horizontal segment of the intraparietal sulcus (Corbetta et al, 1998;Gitelman et al, 1999;Lepsien and Pollmann, 2002;Liu et al, 2003;Pollmann and von Cramon, 2000;Pollmann et al, 2000b;Weidner et al, 2002;Yantis et al, 2003), and with studies of prehensile movements (Binkofski et al, 1998(Binkofski et al, , 1999; and it is consistent with studies of motor attention (Rushworth et al, 2001), which have reported activation along the ascending segment of the intraparietal sulcus and functional deficits following natural lesions or transcranial magnetic stimulation of this segment.…”
Section: Dimension Changesupporting
confidence: 88%
See 2 more Smart Citations
“…Dimension changes further elicited activation along the descending and horizontal segments of the intraparietal sulcus, whereas response changes led to activation in its ascending segment. This distribution is in good agreement with studies of visual attention shifts, both between locations and between features, which have consistently reported activation along the horizontal segment of the intraparietal sulcus (Corbetta et al, 1998;Gitelman et al, 1999;Lepsien and Pollmann, 2002;Liu et al, 2003;Pollmann and von Cramon, 2000;Pollmann et al, 2000b;Weidner et al, 2002;Yantis et al, 2003), and with studies of prehensile movements (Binkofski et al, 1998(Binkofski et al, , 1999; and it is consistent with studies of motor attention (Rushworth et al, 2001), which have reported activation along the ascending segment of the intraparietal sulcus and functional deficits following natural lesions or transcranial magnetic stimulation of this segment.…”
Section: Dimension Changesupporting
confidence: 88%
“…We identified an extended fronto-posterior network phasically activated when the target-defining dimension changed across trials (Pollmann et al, 2000b). This network consists of multiple posterior visual brain areas -including: fusiform gyrus, lateral occipital gyrus, superior temporal sulcus and middle temporal gyrus, superior parietal lobule, and precuneus -that are known to be involved in the attentional modulation of visual processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, electroencephalography (EEG) studies have found that swapping the target and non-target features leads to large delays in the onset of the N2pc (~50ms; Eimer, Kiss & Cheung, 2010), an electrophysiological marker for spatial attentional selection (e.g., Eimer, 1996;Luck & Hillyard, 1994), whereas dimension changes have only small effects on N2pc latencies (~8ms; e.g., Töllner et al, 2008;6ms, Töllner et al, 2010, Rangelov et al, 2013 that cannot account for the substantial RT delay of 30-50ms. Third, functional imaging data show that feature changes lead to an increased BOLD response in early visual areas (e.g., occipital cortex; Kristjansson et al, 2007), whereas dimension changes had no consistent effects on early visual areas, but instead led to increased activation of a dorsolateral pre-frontal network (DLPFC; Gramann et al, 2007Gramann et al, , 2010Pollmann et al, 2000Pollmann et al, , 2006Weidner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the results to date are based on a collection of studies that used different methods and stimuli to examine feature-versus dimension-based switch costs (e.g., Gramann et al, 2007Gramann et al, , 2010Kristjansson et al, 2007;Töllner et al, 2008Töllner et al, , 2010Pollmann et al, 2000, Weidner et al, 2002. Hence, it is unclear whether the observed differences between feature-and dimension-based switch costs were due to differences in the mechanisms tapped or the methods employed for each switch condition.…”
Section: Introductionmentioning
confidence: 99%